Carl Darling Buck, A Dictionary of selected synonyms in the principal Indo-European languages. A contribution to the history of ideas, with the co-operation of colleagues and assistants. University Press, Chicago, 1949. xix + 1515 págs. - Meriggi, Piero (El Colegio de México, 1952)
Se reseñó: A Dictionary of selected synonyms in the principal Indo-European languages. A contribution to the history of ideas, with the co-operation of colleagues and assistants.